FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Sarah Anggraeni Dibah Ayu; Andi Kartika (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aimed to examines the influence of leverage, institutional ownership, audit commitee, sales growth, profitability and firm size on the tax avoidance. This research was conducted at Indonesia by using analysis unit manufacture company that have gone public. The population of this research are manufacture company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2014 until 2017 and obtained as many as 127 companies. The technique of data analysis is used multiple regression analysis. The results of this study shows that leverage, Institutional Ownership and Audit Commitee positive not significant on Tax Avoidance. Sales Growth negative not significant on Tax Avoidance. Profitability positive significant on Tax Avoidance. Firm Size negative significant on Tax Avoidance. Keyword: Leverage, Institutional Ownership, Audit Commitee, Sales Growth, Profitability, Firm Size and Tax Avoidance